Stress distribution on short implants with different designs: a photoelastic analysis - Goiato, Marcelo Coelho [UNESP]; de Medeiros, Rodrigo Antonio [UNESP]; Sônego, Mariana Vilela [UNESP]; de Lima, Taynara Maria Toito [UNESP]; Pesqueira, Aldiéris Alves [UNESP]; dos Santos, Daniela Micheline [UNESP] (Taylor & Francis, 2017)
Short dental implants have been used as an attempt to avoid bone grafts surgery, however there are few literature reports that evaluate changes to their design. Therefore, the aim of this study was to assess the effect of different short implant design on stress distribution through photoelastic analysis. Six external hexagon (5 × 5 mm) short dental implants with different design were used. Each group was treated with a single crown and a three element fixed partial dental prosthesis, resulting in a total of 12 photoelastic models. The assembling photoelastic model-implant-prosthesis was set in a circular polariscope where loads of 100N were applied on the occlusal surface with a Universal Test Machine (UTM). The tension fringes were photographed and later assessed qualitatively by a graphic software (Adobe Photoshop). Less high-intensity fringes were observed on the short implants with triangular threads, short external hexagon and flat apical profile. In conclusion, the macrodesign influenced the amount of stress distributed to the bone when short dental implants are placed.
Keywords: biomechanics; Dental implants; fixed partial prosthesis